Musculoskeletal Interventional Radiology in the Pediatric Population: State of the Art - Arrigoni, Francesco; Izzo, Antonio; Bruno, Federico; Palumbo, Pierpaolo; De Filippo, Massimo; Zugaro, Luigi; Masciocchi, Carlo; Barile, Antonio (Seminars in Musculoskeletal Radiology, 2021)
Interventional radiology procedures have been proven to be as effective as traditional surgery but usually are characterized by lower morbidity rates. In this article, the most diffuse IR treatments for pediatric lesions are reviewed with the aim of describing main advantages and drawbacks. Ablation procedures (in particular RFA and MRgFUS) are widely used for the management of osteoid osteoma and osteoblastoma whereas intracystic injection of methylprednisolone acetate is performed for simple bone cysts. Sclerosing agents and where possible, selective arterial embolization are used for treatment of aneurysmal bone cysts and other vascular malformations. In the management of malignant muscoloskeletal tumors, the role interventional radiology is mainly represented by percutaneous biopsies, and by adiuvant selective embolizations in presence of hypervascular lesions to be submitted to surgery.
Keywords: interventional MSK radiology; pediatric MSK radiology; osteoid osteoma; osteoblastoma; vascular malformations; aneurismal bone cysts; simple bone cysts